Réponses

Meilleure réponse !
2014-05-24T17:19:10+02:00
A = 17/(18)+3*1/6
A = 17/18 + 3/6
A = 17/18 + 9/18
A = 26/18
A = 13/9

B=14/11 - 2/11 * 5
B=14/11 - 10/11
B=4/11

C=1-(5/8-1/4)
C=1-3/8
C=5/8

D=3/4 * 16/9 - 10/6 * 1/6
D= 4/3 - 5/18
D=24/18 - 5/18
D=19/18
2014-05-24T17:24:27+02:00
Re bonjour

A = 17/18 + 3 x 1/6
A = 17/18 + 3/6
A = 17/18 + 9/18 = 26/18 = 13/9

B = 14/11 -2 /11 x 5
B = 14/11 - 10/11 = 4/11

C = 1 - (5/8 -1/4)
C = 1 - (5/8 - 2/8)
C = 1 - 3/8
C = 8/8 - 3/8 = 5/8

D = 3/4 x 16/9  -10/6 x 1/6
D = 1/1 x 4/3 - 10/6 x 1/6
D = 4/3 - 10 /36
D = 48/36 - 10/36 = 38/36 = 19/18